Effects of group reminiscence on elderly depression: A meta-analysis - Dan Song; Qin Shen; Tu-Zhen Xu; Qiu-Hua Sun (Elsevier, 2014)
Background/purpose: The present meta-analysis was performed to evaluate the effectiveness of group reminiscence on depression in elderly patients. Methods: Published and unpublished randomised controlled trials that assessed the effects of group reminiscence on depression in elderly patients were systematically reviewed using multiple electronic databases. Relative risks for dichotomous data and weighted mean differences for continuous data were calculated with 95% confidence intervals. Results: Ten trials were evaluated. Group reminiscence provided significantly greater relief of depressive symptoms than did the control intervention immediately after and 3 months after the intervention (p < 0.00001). However, this advantage disappeared 6 months after the intervention (p = 0.14). Group reminiscence significantly improved self-esteem and life satisfaction (p < 0.01). Conclusion: Group reminiscence was associated with short-term depression relief among elderly patients with depression and effectively improved self-esteem and life satisfaction. Higher-quality large-scale randomised controlled trials are needed to confirm these findings.